Implementación de un data center académico virtualizado - Yrigoyen Quintanilla, Manuel (2015)
This article is based on research conducted by the authors between 2011 and 2012, in the framework of the implementation of research projects, sponsored by the Scientifi c Research Institute of the University of Lima (IDIC). In such research, the technological evolution of the Datacenter was analyzed, and the creation of the technology and management aspects of a Virtualized Datacenter (DCV) were proposed, in order to provide services for the development of laboratories in the academic university fi eld. The findings of this research were applied in the planning process of the “Laboratory Datacenter” of the Systems Engineering Career at the University of Lima, which was used in implementing the new syllabus.